The Relationship Between Parental Mediation, Family Functioning, and Parental Digital Literacy with Children's Gadget Use - Sarini Sarini; Nyimas Heny Purwati; Anita Apriliawati; Desty Lismayanti (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2024)
Background: Excessive use of gadgets among children has negative impacts, such as reduced social interaction, learning disorders, sleep disturbances, vision problems, and radiation risks. Parental mediation strategies and digital literacy can help prevent excessive gadget use in children. Objective: This study aims to determine the relationship between parental mediation, family functioning, and parental digital literacy with gadget use among school-aged children. Methods: The research design employed a descriptive analytic approach with a cross-sectional method. The study sample consisted of school-aged children from elementary schools in Karawang District, selected using purposive sampling with a total of 149 respondents. Data analysis was conducted using the chi-square test followed by multiple logistic regression with a significance level of < 0.05. Results: The study results showed that, in the bivariate analysis, there was a relationship between parental mediation, family functioning, and parental digital literacy with gadget use among children (p-value < 0.05). The multiple logistic regression test results indicated that the variable most associated with gadget use among children was parental mediation. Conclusion: This study is expected to serve as a reference for nurses to assist parents in applying parental mediation techniques and enhancing digital literacy socialization to prevent excessive gadget use in children.